Pengaruh Citra Merek, Kepercayaan Dan Nilai Pelanggan Terhadap Kepuasan Pelanggan Pengguna Gojek Di Kota Batam - Devy Anggraini; Husda, Nur Elfi (LPPM Universitas Putera Batam, 2024)
This research seeks to explore the influence of brand image, trust and customer value on customersatisfaction of Gojek users in Batam City. This research is an associative type with a quantitative approach.Focus on the Gojek consumer population in Batam City, with a total of 6,180 customers. The samplingtechnique chosen was based on the Slovin formula, producing 376 respondents. By using a multiple linearregression approach, the data analysis process includes various tests, such as data quality tests, classicalassumption tests, influence tests, and hypothesis tests. The results of multiple linear regression analysishave been able to show that brand image has an influence of 23.7% on customer satisfaction. Trust showsan influence of 27.9% on customer satisfaction. Customer value can have a big influence of 28.3% oncustomer satisfaction. The test results contained in the analysis of the coefficient of determination (R2)underline the collective explanatory power of brand image, trust and customer value, which accounted for70.7% of the observed variation in customer satisfaction of Gojek users in Batam City. Apart from that, thefindings are also strengthened by using the t test and F test showing that brand image, trust and overallcustomer value have a positive and significant influence both partially and simultaneously on customersatisfaction of Gojek users in Batam City